A Mini-Review of Work Stress and Mindfulness: A Neuropsychological Point of View - González-Palau, Fátima; Medrano, Leonardo Adrián (Frontiers in Psychology, 2022)
Work stress is consistently linked with the deterioration of cognitive and mental health, limitations in everyday workplace performance, and an increased risk of developing diseases. A common thread binding these consequences appears to be stress-associated alterations in neuropsychological functions and affective domains, especially those reliant on hippocampal, prefrontal, and amygdala brain area. Although research broadly supports the claim that the practice of mindfulness meditation for the reduction of the consequences of stress and the promotion of health exert positive effects on workplaces, the precise neuropsychological benefits of Mindfulness-based interventions (MBIs) in the context of organizations remain elusive. In this review, we will analyze the impairments imposed by stress on the brain areas and functions and the benefits of MBIs from a neuropsychological point of view. This is significant since there is a centrality of cognitive functions in core processes necessary for work achievements, such as emotion regulation, problem-solving, and learning. The promotion of wellbeing is a responsibility shared between workers and organizations. Developing healthy environments allows workers to exercise greater control over their work, face work challenges, work productively and develop their talent.